2017
DOI: 10.1111/jan.13341
|View full text |Cite
|
Sign up to set email alerts
|

Inner strength and its relationship to health threats in ageing—A cross‐sectional study among community‐dwelling older women

Abstract: Mental ill health has overall the strongest association with weaker inner strength. Longitudinal studies are recommended to confirm the results. However, the ISS does not only estimate inner strength but can also be a tool for discovering where (i.e. dimension) interventions may be most profitable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Applying this theory to explore the inner strength of community dwelling older women, they found women with higher inner strength, as measured using the Inner Strength Scale (Lundman et al, 2011), had better physical health, and their social relationships were more satisfying. Subsequent studies have found stronger inner strength is associated with less risk of experiencing depression and feeling lonely in older women (Boman, Gustafson, Häggblom, Fischer, & Nygren, 2015;Boman, Lundman, Nygren, Årestedt, & Fishcer, 2017). Janssen, Regenmortel and Abma (2011) do not provide a definition of what they mean by strength, but identified sources of strength that give rise to resilience in older people receiving longterm community care.…”
mentioning
confidence: 99%
“…Applying this theory to explore the inner strength of community dwelling older women, they found women with higher inner strength, as measured using the Inner Strength Scale (Lundman et al, 2011), had better physical health, and their social relationships were more satisfying. Subsequent studies have found stronger inner strength is associated with less risk of experiencing depression and feeling lonely in older women (Boman, Gustafson, Häggblom, Fischer, & Nygren, 2015;Boman, Lundman, Nygren, Årestedt, & Fishcer, 2017). Janssen, Regenmortel and Abma (2011) do not provide a definition of what they mean by strength, but identified sources of strength that give rise to resilience in older people receiving longterm community care.…”
mentioning
confidence: 99%
“…This implicates that psychological flexibility can be seen as an important underlying mechanism with significant associations with both trait gratitude and loneliness. Findings in limited prior research support a positive association between gratitude and psychological flexibility (Fredrickson, 2004;Hill, 2011;Kashdan & Rottenberg, 2010) and a negative association between psychological flexibility and loneliness (Boman et al, 2017;Gardiner et al, 2018;Hamama-Raz & Hamama, 2015). In addition, results revealed that engaged living partly mediates the association between gratitude and loneliness in middle-aged and older adults when it is included as a single mediator.…”
Section: Discussionmentioning
confidence: 75%
“…The first four processes represent the Acceptance process and the last two processes represent the Commitment process in ACT (ACT; Hayes, Luoma, Bond, Masuda, & Lillis, 2006). Because previous research has demonstrated that psychological flexibility decreases with age (Boman, Lundman, Nygren, Årestedt, & Santam€ aki Fischer, 2017;Viglund et al, 2013), it may be beneficial for middle-aged and older adults to strengthen psychological flexibility. However, there is a gap in the literature about psychological flexibility as an underlying mechanism in the association between trait gratitude and loneliness.…”
Section: The Role Of Psychological Flexibility and Engaged Livingmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, people with a higher degree of inner strength reported better self-rated health despite their disease (Viglund et al 2014 ). In a group of older women, inner strength was found to be positively related to physical and mental health (Boman et al 2017 ) and, conversely, negatively related to signs of depression (Boman et al 2015b ). Higher scores of inner strength showed an association with better subjective and objective health and more social contacts, in a group of very old people (Lundman et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%